Analisis Korelasi Untuk Menentukan Hubungan Literasi Sains Dan Motivasi Berprestasi Terhadap Hasil Belajar Pendidikan Agama Islam - Athaya Rahmah; Syahidah Rena; M. Ubaidillah Al-Ghifary (Al-Munawwarah : Jurnal Pendidikan Islam, 2021)
Abstract: Islamic education in vocational schools lately is still less encouraging. In terms of learning outcomes and motivation to excel in the lesson is still relatively low when compared to other lessons, especially vocational lessons. Islamic Religious Education learning is also less associated with science. This is exacerbated by the results of science literacy by PISA (International Student AssessmentProgram) obtained by our country is also very low. Therefore it is considered necessary to improve Islamic Religious Education through the motivation of achievement and science literacy. The purpose of this study is to find out the correlation between science literacy and motivation of achievement with the results of learning Pendidikan Agama Islam. The methodology the authors used in this study was descriptive quantitative with correlational analysis methods. Data analysis techniques of the results of the study using pearson productmoment correlation technique. The results of correlation analysis test resulted in a positive and significant correlation between science literacy and motivation of achievement with the results of learning Pendidikan Agama Islam, obtained product moment coefficient price (R) of 0.306 with the contribution of science literacy, motivation to achieve the results of learning Pendidikan Agama Islam by 9.40% and the remaining 91.60% contributed by other factors. This study can be concluded that variables X1 and X2 have a simultaneous and significant effect on Y, the value of r2 from correlation X1X2 with Y of 0.094 means, variable X1X2 produces a positive correlation with variable Y.